How the design of cartel fines affects prices: Evidence from the lab - Sindri Engilbertsson; Sander Onderstal; Leonard Treuren (Tinbergen Institute, 2025)
Competition authorities impose substantial penalties on firms engaging in illegal pricefixing. We examine how basing cartel fines on either revenue, profit, or price overcharge influences cartel and market prices, as well as cartel incidence and stability. In an infinitely repeated Bertrand oligopoly game, we show that revenue-based fines incentivize firms to charge prices above the monopoly price, whereas only overcharge-based fines encourage prices below the monopoly price. Cartels are stable for a smaller range of discount factors when fines are based on overcharges rather than other bases. We test these predictions in a laboratory experiment where subjects can form cartels, which allows them to discuss pricing at the risk of being detected and fined. By equalizing expected fines across treatments, we isolate the effect of the fine's base. We find that market prices are lowest under overcharge-based fines and highest under revenue-based fines. Variation in market prices across treatments is fully driven by cartel prices. While these results align with the theoretical predictions, cartel incidence remains unchanged across regimes. Our results suggest competition authorities could improve enforcement by shifting from revenue-based fines to profit- or overcharge-based fines.
Keywords: C73; C92; D43; K21; L41; 330; Antitrust; Cartel; Collusion; Repeated game; Experiment